Insights on Multiple Myeloma Treatment Strategies - Mateos, María-Victoria; Ludwig, Heinz; Bazarbachi, Ali; Beksac, Meral; Bladé, Joan; Boccadoro, Mario; Cavo, Michele; Delforge, Michel; Dimopoulos, Meletios A; Facon, Thierry; Geraldes, Catarina; Goldschmidt, Hartmut; et al. (HemaSphere, 2019)
The introduction of new agents and management strategies over the past decade has resulted in a major step change in treatment outcomes with deepening responses and increased survival for patients with multiple myeloma. In daily clinical practice, healthcare professionals are now faced with challenges including, optimal treatment sequencing and changing treatment goals. In light of this, a group of experts met to discuss diagnostic and treatment guidelines, examine current clinical practice, and consider how new clinical trial data may be integrated into the management of multiple myeloma in the future.